Consumer Purchasing Intentions and Marketing Segmentation of Remanufactured New-Energy Auto Parts in China. (2nd July 2020) - Zhang, Shibin; Zhou, Chuhan; Liu, Yanran
Abstract : This study tests and verifies the main factors influencing consumers' intention to purchase and the marketing strategy of remanufactured new-energy automobile parts in China. The revised model of Theory of Reasoned Action is used to study the factors influencing consumers' intention to purchase. The main factors influencing consumer purchase intention of remanufactured new-energy automobile parts in China are identified through correlation analysis of factors including subjective norms, attitudes, face consciousness, brand extension, and perceived risk. Through market segmentation, consumers in China are divided into three types: passive-accepted, brand-driven, and green-consuming; the marketing strategy is developed accordingly. This study provides theory and decision-making basis for remanufactured new-energy automobile parts markets.